Peranan Ekonomi Digital pada E-Commerce dalam Meningkatkan Pendapatan UMKM (Studi Kasus UMKM Fashion di Sangatta): Penelitian - Selly Swandari; Akbar Lufi Zulfikar; Nurfiza Widayati; Muhammad Awaluddin; Priskila Angel (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the role of digital economy in e-commerce in increasing the income of SMEs, particularly in the fashion sector, with a case study on fashion SMEs in Sangatta. Using a qualitative research method, data was collected through interviews with SME owners selling fashion products on the Shopee e-commerce platform. The results indicate that the implementation of e-commerce, especially through Shopee, has a positive impact on SME income. Most informants reported a significant increase in product sales after joining Shopee, with percentage increases ranging from 20% to 80%. This shows that e-commerce plays an important role in expanding the market for SMEs and boosting their income, in line with the advancement of digital technology that facilitates online buying and selling transactions. The study also highlights the importance of using Shopee features, such as free shipping and other promotions, in attracting consumer attention and driving increased sales.